GROWTH PERFORMANCE OF NILE TILAPIA (Oreochromis niloticus) FRY IN THE STAGNANT WATER POND SYSTEMS WITH DIFFERENT FEEDING RATES - Djauhari, Ricky; Sylvia Monalisa, Shinta; Sena Wahyuni, Amaya; Christiana, Ivone; Gunawan, Irawadi; Senas, Petrus; Asi Nion, Yanetri; Toteles, Aris; Sadelman Tulis, Riamona; Sarie, Fatma; Simamora, Lamria; Zulaika, Tatik; et al. (Jurnal Perikanan Unram, 2024)
The activity of cultivating nile tilapia in a stagnant water pond system allows fish to utilize resources in the form of natural food and commercial feed in a balanced manner, thereby reducing the amount of external feed. This research aims to evaluate the growth performance of tilapia fry in a stagnant water pond system with different feeding levels. This research was carried out using a completely randomized design (CRD) consisting of 3 treatments for rearing tilapia fry in a stagnant water pond system with different feeding levels with three replications each, namely 3% feeding rate, 4.5% feeding rate. % and feeding rate 6%. The test tilapia fish had an average initial weight of 2.66-3.06 g and were reared for 21 days with feed supplementation containing a commercial probiotic mix dose of 0.2% and a feeding frequency of 1 time per day. The results of the research showed that different levels of feeding had a significant effect (p<0.05) on feed efficiency, feed conversion ratio and amount of feed consumption, but could still provide optimum growth rates.